2018
DOI: 10.1146/annurev-genom-083117-021256
|View full text |Cite
|
Sign up to set email alerts
|

Common and Founder Mutations for Monogenic Traits in Sub-Saharan African Populations

Abstract: This review highlights molecular genetic studies of monogenic traits where common pathogenic mutations occur in black families from sub-Saharan Africa. Examples of founder mutations have been identified for oculocutaneous albinism, cystic fibrosis, Fanconi anemia, and Gaucher disease. Although there are few studies from Africa, some of the mutations traverse populations across the continent, and they are almost all different from the common mutations observed in non-African populations. Myotonic dystrophy is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…cystic fibrosis, beta-thalassaemia and Fanconi anaemia, to name a few. [46] The challenges are significant, not least of which is the cost of such treatments. We must also acknowledge the health burden in SA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cystic fibrosis, beta-thalassaemia and Fanconi anaemia, to name a few. [46] The challenges are significant, not least of which is the cost of such treatments. We must also acknowledge the health burden in SA.…”
Section: Resultsmentioning
confidence: 99%
“…Using a modified version of CRISPR (CRISPR-Cpf1), Zhou et al [45] were able to identify suitable endonucleases that would allow repair of this mutation, leading to restoration of SMN protein in patient-specific iPSCs.However, it is estimated that only 50% of patients in SA have the homozygous deletion mutation exhibited globally, due to the complexities of the genomic rearrangements of the region. [46] Furthermore, they reveal frequent deletions of SMN2, [47] suggesting targeting of SMN2 to restore SMN protein will have limited impact in SA patients. Therefore, if iPSC technology using SA SMA patient-specific cells could be generated, rescue of the mutation could reveal whether these unique patients would benefit from genome engineering targeting the SMN2 gene rearrangement.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…The unadjusted estimated global prevalence of DM1 was 9.27 cases per 100,000 (95% CI: 4.73-15.21), while the region-adjusted pooled prevalence was 9.02 cases per 100,000 (95% CI: 5.60-13.17). Although ethnicity information was not explicitly mentioned in the included studies, previous studies have shown that the prevalence of DM1 is altered in different ethnicities [38][39][40]. It has been acknowledged that DM1 is more common in populations with European ancestry, while it is rare and even absent in Southern Africa [39,40], which may be partly explained by the low frequency of long CTG repeats within the normal range in the Southern African population [41].…”
Section: Discussionmentioning
confidence: 99%
“…Although ethnicity information was not explicitly mentioned in the included studies, previous studies have shown that the prevalence of DM1 is altered in different ethnicities [38][39][40]. It has been acknowledged that DM1 is more common in populations with European ancestry, while it is rare and even absent in Southern Africa [39,40], which may be partly explained by the low frequency of long CTG repeats within the normal range in the Southern African population [41]. Regarding the prevalence in Asia, the estimated prevalence of DM1 was low in Taiwan and Hong Kong [28,29] with 0.45 cases and 0.37 cases per 100,000, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in deafness genes have diverse patterns and ethnicity-specific features. In Sub-Saharan African populations, common deafness does not arise from mutations in GJB2 and GJB7 but may arise from mutations in HTT and JPH3 (Krause, Seymour, & Ramsay, 2018). Mutations associated with genetic deafness are located in GJB2, SLC26A4, and OTOF in the Pakistani population and in GJB2, TMC1, and CDH23 in the Indian population (Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%